ENDOTHELIAL DYSFUNCTION PATHOGENETIC SIGNIFICANCE AND ITS MARKERS PROGNOSTIC IMPORTANCE IN SPONTANEOUS ARTERIAL HYPERTENSION - Polyvanova, N.P.; Savytskyi, I.V.; Hrytsan, I.I.; Savytskyi, V.I.; Yatsyna, O.I.; Kulynych, G.B.; Sarakhan, V.M. (World of Medicine and Biology, 2024)
The purpose of the study was to investigate the diagnostic importance of main endothelial dysfunction biomarkers in experimental arterial hypertension with an inflammatory component in its pathogenesis. Blood levels of von Willebrand factor, plasminogen activator inhibitor 1, endothelin 1, and soluble vascular cell adhesion molecule 1 occurred to be significantly increased in rats with spontaneous arterial hypertension. The endothelial dysfunction markers selected for this study are the substances that evidently highlight its specific pathogenetic mechanisms and consequently the mechanisms of arterial hypertension development. The data obtained highlighted endothelial dysfunction complex mutually reinforcing pathogenetic mechanisms were detected, which showed its pathogenesis complexity and multi-component nature and reflected the diverse body systems pathological dysfunction systemic nature. The authors concluded that adequate and effective therapy for arterial hypertension should consider the identified pathogenetic mechanisms and be aimed at endothelial dysfunction development prevention and progression.